2022
DOI: 10.3390/nu14142985
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Screen Time on Dietary Habits and Physical Activity in Children and Adolescents

Abstract: Background: Over the last few decades, the time children spend using electronic devices has increased significantly. The aim of the study was to evaluate the impact of screen time on dietary behaviors and physical activity in children and adolescents. Methods: An online survey was conducted among parents of preschool and school-aged children during the COVID-19 lockdown in Poland. There were 3127 surveys used in the analysis. Results: Survey responses referred to 1662 (53%) boys and 1465 (47%) girls, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
2
25
2
Order By: Relevance
“…12 More than 80% of preschool children use screen devices more than the recommended time, 13 whereas most of the children used their devices during meals. 6 The average sleeping time of children before the pandemic has decreased by more than 1 hour compared with the previous century. 14 Teaching-learning activities in schools of Nepal 15 have forcefully changed classroom teaching to screendependent online education, which continued for a few months each year with the rise of COVID-19 cases.…”
Section: What This Study Addsmentioning
confidence: 99%
See 3 more Smart Citations
“…12 More than 80% of preschool children use screen devices more than the recommended time, 13 whereas most of the children used their devices during meals. 6 The average sleeping time of children before the pandemic has decreased by more than 1 hour compared with the previous century. 14 Teaching-learning activities in schools of Nepal 15 have forcefully changed classroom teaching to screendependent online education, which continued for a few months each year with the rise of COVID-19 cases.…”
Section: What This Study Addsmentioning
confidence: 99%
“… 12 More than 80% of preschool children use screen devices more than the recommended time, 13 whereas most of the children used their devices during meals. 6 The average sleeping time of children before the pandemic has decreased by more than 1 hour compared with the previous century. 14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More exploratory studies are needed because the relationship between the frequency of watching food-related content, watching motivation, and diet has been reported [ 25 , 27 ]. A recent study also reported that media watching affects adolescents’ dietary habits, and that wise use of media is necessary to form healthy eating habits [ 36 ]. However, the relationship between food-related content, among various contents types, and adolescents’ eating habits has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%